Implementation of CSR Activities from Stakeholder Theory Perspective in Wika Mengajar - Zain, Ratna Ningrum Wulandani; Hendriyani, Chandra; Nugroho, Danang; Ruslan, Budiana (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2021)
The purpose of this research is to explore Corporate Social Responsibility (CSR) activities in the stakeholder theory point of view in the WIKA Mengajar program. The needs of stakeholders both internally and externally in relation to social and environmental responsibility through the triple bottom line model is one way to explore CSR activities. This research was conducted using phenomenological methods with a qualitative approach at PT Wijaya Karya (Persero) Tbk. (WIKA). Interviews are conducted with the General Manager of Corporate Relations, collecting evidence in the form of documentation and articles of activities that are then simplified to produce relevant information. The results of the study showed the benefits of CSR through the point of view of internal stakeholder theory of the company always maintaining commitment and meeting the needs of stakeholders both internally and externally, in this case WIKA shows social and environmental responsibility that includes economic, social, and environmental aspects (triple bottom line) through CSR activities.